Tissue Regeneration Capacity of Extracellular Vesicles Isolated From Bone Marrow-Derived and Adipose-Derived Mesenchymal Stromal/Stem Cells - Liu, Yuan; Holmes, Christina (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stem cell (MSC)-based therapies have demonstrated tissue repair and regeneration capacity in various preclinical models. These therapeutic effects have recently been largely attributed to the paracrine effects of the MSC secretome, including proteins and extracellular vesicles (EVs). EVs are cell-secreted nano-sized vesicles with lipid bilayer membranes that facilitate cell-cell signaling. Treatments based on MSC-derived EVs are beginning to be explored as an alternative to MSC transplantation-based therapies. However, it remains to be determined which MSC source produces EVs with the greatest therapeutic potential. This review compares the tissue regeneration capacity of EVs isolated from the two most common clinical sources of adult MSCs, bone marrow and adipose tissue, with a particular focus on their angiogenic, osteogenic, and immunomodulatory potentials. Other important issues in the development of MSC-derived EV based therapies are also discussed.